1987
DOI: 10.1021/ma00167a009
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative binding of sodium myristate to amylose

Abstract: The binding of sodium myristate to amylose has been studied by a surface tension method. Surface tensions of myristate solutions were compared with those of systems containing amylose. Slow adsorption of amylose-myristate complex at the air-water interface has rendered possible the use of surface tension for estimating mean activities of sodium myristate in the presence of amylose and the construction of a binding isotherm. Information has also been gained on the "surface activity" of complexes. Comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…In more general terms, this approach also adds to a series of techniques used previously to probe the amylose conformation in solutions and its versatility to complex with a variety of other molecules: 13 C-NMR spectrometry [13], circular dichroism [14], viscometry [8], calorimetry [15], potentiometry [16], and surface tension measurements [17]. In describing the complexation phenomena between the amylose oligomers and various pharmaceuticals [18], we have recently demonstrated the value of this electrophoretic approach: (i) it provides ªoligomer-specific informationº, for which the bulk measurements are not informative; (ii) capillary zone electrophoresis (CZE) is inherently a sensitive technique, necessitating only minute quantities of studied materials; and (iii) CZE overcomes any potential problems with a limited solubility of amylose and its complexes that may complicate less sensitive bulk measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In more general terms, this approach also adds to a series of techniques used previously to probe the amylose conformation in solutions and its versatility to complex with a variety of other molecules: 13 C-NMR spectrometry [13], circular dichroism [14], viscometry [8], calorimetry [15], potentiometry [16], and surface tension measurements [17]. In describing the complexation phenomena between the amylose oligomers and various pharmaceuticals [18], we have recently demonstrated the value of this electrophoretic approach: (i) it provides ªoligomer-specific informationº, for which the bulk measurements are not informative; (ii) capillary zone electrophoresis (CZE) is inherently a sensitive technique, necessitating only minute quantities of studied materials; and (iii) CZE overcomes any potential problems with a limited solubility of amylose and its complexes that may complicate less sensitive bulk measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that a cooperative binding is the complexation process between amylose and guest molecules,19,20 implying the possibility of conformational change (induced by guest) in amylose due to the complexation. Some studies of this aspect have been made by surface tension and viscosity measurements of surfactants.18, 20 In this paper, we make a systematic assessment of complexation behavior of amylose with photoreactive dyes having a stilbazolium chromophore, based on spectroscopic studies of UV-vis, fluorescence, and circular dichroism (CD) in various compositions of DMSO-H20 mixtures. Molecules with this chromophore have the largest secondorder polarizabilities21 such that nonlinear optical materials based on this chromophore have been studied in recent years.22,23 A potential benefit of inclusion formation of photoreactive dyes is to induce photo-and thermal stability to the dyes through chemical rigidization and shielding of the guest molecules by host, amylose.24 (15) Ring, S. G.; L'Anson, K. J.; Morris, V. J. Macromolecules 1985, 18, 182.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been employed to explore the conformation of amylose in aqueous solutions: 13 C NMR, 21,29 circular dichroism, 30 viscosity 18 and potentiometric 27 measurements, calorimetry, 31 spectrophotometry, 17,20 use of a fluorescent probe, 32 and surface tension measurements. 26 While X-ray data have clearly shown amylose featuring strictly helical forms in its crystalline state, 1 the situation in aqueous solutions is somewhat nebulous. The three forms that were suggested 18,20 to describe the conformation of amylose in aqueous solutions include a helix, an extended helix, and a random coil.…”
mentioning
confidence: 99%